Studies of Malaysian plants in prevention and treatment of colorectal cancer - Hashim, Yumi Zuhanis Has-Yun; Gill, Chris I.R.; Latimer, Cheryl; Ternan, Nigel G.; Abbas, Phirdaous (Tech Open, 2016)
Incidence rates vary 10-fold globally for colorectal cancer (CRC). Asia has lower rates than Western countries, but as the Western life-style becomes more prevalent in economically developing Asian countries, rates are increasing. Clinical therapy has improved over the last few decades, and national screening programmes are a proven and effective means of reducing mortality; chemoprevention through diet and life-style choices may provide additional value. Diet has strong associations with the aetiology of CRC, considerable epidemiological evidence exist that fruits and vegetables are associated with reduced risk of CRC. There is also extensive experimental evidence that phytochemicals from fruit and vegetables can modulate pathways of carcinogenesis. In this chapter, we consider Malaysia specifically, with its rich ethnopharmacological heritage and megabiodiversity; Malaysian natural compounds may be a source of potentially chemo-protective with relevance to CRC.